Internet connectivity disruption in Tanzania (Tanzania) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Tanzania. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: TZ-2026-0041. Severity: critical. Confidence: 65%